Sorting it out: bedding particle size and nesting material processing method affect nest complexity. (April 2017) - Robinson-Junker, Amy; Morin, Amelia; Pritchett-Corning, Kathleen; Gaskill, Brianna N
As part of routine husbandry, an increasing number of laboratory mice receive nesting material in addition to standard bedding material in their cages. Nesting material improves health outcomes and physiological performance in mice that receive it. Providing usable nesting material uniformly and efficiently to various strains of mice remains a challenge. The aim of this study was to determine how bedding particle size, method of nesting material delivery, and processing of the nesting material before delivery affected nest building in mice of strong (BALB/cAnNCrl) and weak (C3H/HeNCrl) gathering abilities. Our data suggest that processing nesting material through a grinder in conjunction with bedding material, although convenient for provision of bedding with nesting material 'built-in', negatively affects the integrity of the nesting material and subsequent nest-building outcomes. We also found that C3H mice, previously thought to be poor nest builders, built similarly scored nests to those of BALB/c mice when provided with unprocessed nesting material. This was true even when nesting material was mixed into the bedding substrate. We also observed that when nesting material was mixed into the bedding substrate, mice of both strains would sort their bedding by particle size more often than if it were not mixed in. Our findings support the utility of the practice of distributing nesting material mixed in with bedding substrate, but not that of processing the nesting material with the bedding in order to mix them.